Abuelos at home: Differential impact on children's education by family structure. (December 2017) - Arenas, Erika
Highlights: I used a sequential logit model to study grandparent's influence on grandchildren's education. Grandparent's co-residence had an influence depending on family structure. Grandparent's education did not have an influence on children's educational transitions. Interaction between parent's and grandparent's education were not significant. The influence of co-resident grandparent's did not depend on their educational level. Abstract: Improvements in life expectancy have increased interactions between grandchildren and grandparents. This paper examines how grandparent's co-residence shapes grandchildren's educational progression by grandchildren's family structure. Based on a life course perspective approach, I use three waves of novel panel data from the Mexican Family Life Survey, and ask whether grandparent's co-residence influence grandchildren's educational transitions, depending upon grandchildren's family structure, and whether grandparents' education influence grandchildren's educational transitions. This study suggests that grandparents' co-residence does not have a linear effect on the process of educational attainment, given that its effect maybe positive, negative, of null depending on family structure and the specific roles grandparents assume. It also shows that in countries like Mexico, where the education of older cohorts is fairly low, grandparent's education is not associated with grandchildren's school progression.